Influence of Cooking Temperature on the Moisture Content and Organoleptic Properties of Pineapple, Banana, and Dragon Fruit Jam - Mutia Ardila; Rafidah Almira Samosir; Alfira Julian Pratiwi; Ekin Dwi Arif Kurniawan; Najwa Putri L. Nasution; Gresvita Sanova Turnip; Sari Mawaddah; Faizah A. Nasution; Feri P. Jahata Samosir; Moondra Zubir; Abd Hakim S (Universitas Negeri Medan, 2025)
Jam is a processed fruit product with high density and acidity, making it more stable than other fruit-based products. The jam-making process includes crushing the fruit, adding sugar, acid, thickening agents, and applying heat. Cooking temperature plays a critical role in determining the moisture content, texture, aroma, and taste of jam. This study investigates the influence of cooking temperature on the moisture content and organoleptic properties of pineapple (Ananas comosus), banana (Musa paradisiaca), and dragon fruit (Hylocereus spp.) jams. The jams were prepared by heating at various temperatures (900C, 1000C, 1100C), followed by moisture content measurement and organoleptic testing. Results showed that higher temperatures significantly reduced moisture content and enhanced sensory quality. Jams cooked at 110°C had the lowest moisture levels and the best organoleptic scores. These findings highlight the importance of temperature control in producing high-quality jam.